Unraveling Audit Fee Dynamics: How Auditor Reputation Moderates Corporate Attributes in the Middle Eastern Landscape - Boli, Hubertus Ade Resha Raditya; Amanda, Silvisia (AKUNSIKA: Jurnal Akuntansi dan Keuangan, 2025)
This study investigates the determinants of audit fees in publicly listed healthcare firms across Middle Eastern stock exchanges during the 2022–2024 period. Specifically, it examines how firm risk, firm size, and firm profitability influence audit fees, with auditor reputation introduced as a moderating variable. Using a dataset of 273 firm-year observations and applying multiple linear regression analysis, the findings reveal that firm size has a significant positive effect on audit fees, while firm profitability and firm risk both exhibit significant negative effects. Additionally, auditor reputation strengthens the positive relationship between firm size and audit fees but does not significantly moderate the relationship between profitability and audit fees. Interestingly, auditor reputation weakens the negative effect of firm risk on audit fees, suggesting nuanced pricing strategies among highly reputable auditors. These results contribute to a deeper understanding of audit fee dynamics within a sector and region that remain underexplored in existing literature. The study also highlights the importance of considering contextual factors such as audit firm reputation when evaluating audit cost structures.